ANALISIS KESANTUNAN BERBAHASA PADA NOVEL BRIANNA DAN BOTTOMWISE KARYA ANDREA HIRATA - Helvy Ranti, Uci; Rukiyah, Siti; Masnunah, Masnunah (Universitas PGRI Palembang, 2023)
Language politeness is essentially our ethics in socialising in society. Politeness rules are generally used in every language act. Theoretically, basically everyone should speak politely. Everyone must maintain ethics in communication so that the purpose of communication can be achieved. In connection with the background discussion of language politeness, it is necessary to analyse the novel Brianna and Bottomwise by Andrea Hirata. The characters and characterizations in this novel are more complex and the dialogues are more frequent so that the maxims in the principles of politeness are more likely to appear. The principles of politeness in speech are: (1) maxim of wisdom, (2) maxim of generosity, (3) maxim of praise, (4) maxim of humility, (5) maxim of agreement, and (6) maxim of sympathy. This research is a literature study using qualitative descriptive method. The primary data is the novel Briana and Bottomwise by Andrea Hirata. The primary data is analysed by using secondary data as supporting data to analyse the novels Briana and Bottomwise according to the research domain of the use of language politeness as required through the supporting references of this research. Keyword: Analysis of Language Politeness